PERLINDUNGAN HUKUM TERHADAP KONSUMEN MELALUI LARANGAN PENCANTUMAN KLAUSULA BAKU - Kingkin Wahyuningdyah (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
Consumer protection is every effort to ensure legal certainty to provide protection to consumers through the principle of balance. Consumer Protection Act Article 18 regulates the ban on the inclusion of standard clauses in the agreement, nsmun not fully reflect the principle of balance between businesses and consumers. Consequently there is no legal protection for consumers. Keywords: Consumer, Consumer Protection, Clause Baku